Mathematical modeling of physiological parameters in traumatic shock caused by lower limb blast injury - I. V. Tolmachev; A. V. Anisin; A. M. Bala; D. A. Vrazhnov; A. V. Shapovalov; M. Yu. Kotlovskiy; V. V. Laptev; K. S. Brazovskiy (Бюллетень сибирской медицины)
The aim of this study was to apply integrative physiological mathematical models to simulate physiological parameters in traumatic shock caused by lower limb blast injury.Materials and methods. At the first stage of mathematical modeling, we applied lumped parameter integrative physiological models, and at the second stage we used neural networks.Results. We developed a clinical decision support system that allows to determine the intensity of blood loss in lower limb blast injuries according to physiological monitoring data.Conclusion. The developed approaches make it possible to partially solve the problem associated with the impossibility of accumulating a sufficient amount of medical data for a specific person to create an adequate personalized clinical decision support system.